A2SbB3O8 (A = Na, K, Rb) and β-RbSbB2O6: two types of alkali boroantimonates with 3D anionic architectures composed of SbO6 octahedra and borate groups. Issue 9 (11th February 2016) - Yan, Dong; Hu, Chun-Li; Mao, Jiang-Gao
Abstract : Two types of 3D boroantimonate frameworks composed of borate clusters and SbO6 octahedra are presented. Abstract : Four new alkali metal boroantimonates, namely, A2 SbB3 O8 (A = Na, K, Rb) and β-RbSbB2 O6, have been synthesized by high-temperature solid-state reactions. Isostructural A2 SbB3 O8 (A = Na, K, Rb) crystallizes in the monoclinic space group P 21 / c, with structures featuring a novel 3D anionic framework composed of SbO6 octahedra and linear B3 O8 groups with 1D tunnels of Sb4 B4 8-membered-rings (MRs) along the a -axis, which are filled by alkali metal ions. β-RbSbB2 O6 crystallizes in the polar space group Cc, revealing novel 3D anionic networks composed of SbO6 octahedra chains and B2 O5 groups with 1D tunnels of Sb4 B2 6-MRs along the b -axis and 1D tunnels of Sb3 B4 7-MRs along the c -axis. Studies on their optical properties and thermal stability, band structure calculations based on DFT methods and linear optical calculations have also been performed.